Retropupillary iris claw intraocular lens implantation in aphakia for dislocated intraocular lens - Faria, Mun Yueh (2020)
© 2016 Faria et al. This work is published and licensed by Dove Medical Press Limited. The full terms of this license are available at https://www.dovepress.com/terms.php and incorporate the Creative Commons Attribution – Non Commercial (unported, v3.0) License (http://creativecommons.org/licenses/by-nc/3.0/).